Environmental Exposure to Toxic Chemicals and Human Health - Fernandes, Virgínia Cruz; Pestana, Diogo (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
It was recently reported that pollution was responsible for 9 million premature deaths in 2015, making it the world's largest environmental risk factor for disease and premature death. Human and industrial activities generate various forms of residual wastes and by-products in a solid, liquid, or gaseous state. Waste generation starts with simple processes such as living, eating, and breathing. Managing waste and minimizing associated environmental impacts have become more challenging as worldwide populations and economies continue to grow. Once these hazardous chemicals are present in the environment, people can become exposed to them. Human health can be influenced by many factors, including exposure to physical, chemical, biological, and radiological contaminants in the environment.This reprint comprises research papers related to the aspects of environmental exposure to multiple toxic chemicals and human health. The manuscripts are focused on toxicology, biomonitoring, exposure and risk assessment, and endocrine disruptors.